The enduring lure of socialism: The politcal economy of the subprime crisis - Dóra Győrffy (Transformation, Integration and Globalization Economic Research (TIGER), 2009)
Market failure and the need for stronger state involvement in the economy has become the dominant perspective in the interpretation of the subprime crisis. After providing a brief description of the various stages of the crisis, the paper challenges this view by showing how monetary, fiscal and regulatory policy in the United States contributed to the crisis through giving rise to false perceptions regarding the magnitude of investment risks among market actors. Furthermore it is also shown that these policies are not due to random mistakes, but rather reflect illusions about technological progress and the possibilities of risk management. The paper's main claim is that whether these beliefs were genuine or served to conceal identifiable political purposes, they should make us equally careful about advocating greater state involvement in the economy.
Keywords: 330; Finanzkrise; Wirtschaftspolitik; Staatliche Einflussnahme; Staat; USA